A novel low power MOSFET-C band pass filter for low frequency applications with subthreshold models based on polynomial regression - ÖZENLİ, DENİZ (SPRINGER, 2018)
A novel current mode MOSFET-C filter is presented for a wide range of low frequency applications ranging from biomedical signal sensing up to speech processing region. Presented filter consumes only 2.3 mu W with symmetrical supply voltages as low as +/- 0.5 V. The filter structure can be easily adjusted by means of changing external capacitor values. Furthermore, proposed filter is given with a novel design methodology based on polynomial regressive small signal models. In this way, promising interaction between design parameters such as V-GS, V-DS, channel width (W), channel length (L) and filter specifications such as f(0), Q and power is provided. Simulation results with 0.18 mu m TSMC CMOS technology are given, furthermore proposed filter is tested to process a real fetal PCG signal at 355.4 Hz. It is shown that proposed filter attains a promising performance in comparison with the previously presented counterparts for low frequency applications.
Keywords: MOS only; MOS-C; Current mode; Polynomial regression; PCG; EMG; ECG; BIOMEDICAL APPLICATIONS; DESIGN